Prevention, diagnosis, and management of donor derived infections in pediatric kidney transplant recipients - Epperson, Katrina; Crane, Clarkson; Ingulli, Elizabeth (Frontiers in Pediatrics, 2023)
Donor derived infections (DDIs) in pediatric kidney transplant recipients remain challenging to diagnose and can result in serious morbidity and mortality. This review summarizes the current guidelines and recommendations for prevention, diagnosis, and treatment of unexpected DDIs in pediatric kidney transplant recipients. We provide a contemporary overview of DDI terminology, surveillance, epidemiology, and recommended approaches for assessing these rare events with an emphasis on the pediatric recipient. To address prevention and risk mitigation, important aspects of donor and pediatric candidate evaluations are reviewed, including current Organ Procurement and Transplantation Network (OPTN) and American Society of Transplantation (AST) recommendations. Common unexpected DDI encountered by pediatric transplant teams including multi-drug resistant organisms, tuberculosis, syphilis, West Nile Virus, toxoplasmosis, Chagas disease, strongyloidiasis, candidiasis, histoplasmosis, coccidioidomycosis, and emerging infections such as COVID-19 are discussed in detail. Finally, we consider the general challenges with management of DDIs and share our experience with a novel application of next generation sequencing (NGS) of microbial cell-free DNA that will likely define a future direction in this field.